Pricing congestible network resources. - MacKie-Mason, J.K (IEEE Journal on selected areas in communications)
We describe the basic economic theory of pricing a congestible resource such as an FTP server, a router, a Web site, etc. In particular, we examine the implications of ?congestion pricing? as a way to encourage efficient use of network resources. We explore the implications of flat pricing and congestion pricing for capacity expansion in centrally planned, competitive, and monopolistic environments. The most common form of Internet pricing is pricing by access, with no usage-sensitive prices. With a fixed set of users, we expect to see greater capacity when usage is not priced, but also greater congestion. However, with greater congestion, congestion-sensitive users might not use the resource